RESPON Trichoderma spp. TERHADAP INDEKS VIGOR BENIH DAN BERAT KERING KECAMBAH PADI VARIETAS SIRANDAH BATUAMPA - Rahmi Zahri Zani; Azwir Anhar (Jurnal Biologi dan Pembelajarannya (JB&P), 2021)
Rice is a staple food crop for some Indonesians. To increase rice production, various efforts have been made, one of which is seed priming using biofertilizers. Biofertilizer or biological fertilizer uses microorganisms that are used as plant growth boosters. The microorganisms used to act as PGPF (Plant Growth Promoting Fungi) are Trichoderma spp. Trichoderma spp. widely used because it can trigger plant growth. This study aims to determine the response of Trichoderma spp. to the seed vigor index and dry weight of rice sprouts of sirandah batuampa variety. The research method is experimental research using a completely randomized design (CRD) with 6 treatments and 3 replications. Parameters observed were seed vigor index and sprouts dry weight. The results showed that Trichoderma spp. had no significant effect on seed vigor index and sprouts dry weight. Judging from the mean value, the seed vigor index of SBT, SRBA, and KRT had better values ​​than the control, as well as the dry weight of sprouts with the provision of SBT, SRBA, and SB isolates. This shows Trichoderma spp. This gave a positive response to the Sirandah Batuampa variety.